Group membership, competition, and altruistic versus antisocial punishment: Evidence from randomly assigned army groups - Lorenz Goette; David Huffman; Stephan Meier; Matthias Sutter (Institute for the Study of Labor (IZA), 2010)
We investigate how group boundaries, and the economic environment surrounding groups, affect altruistic cooperation and punishment behavior. Our study uses experiments conducted with 525 officers in the Swiss Army, and exploits random assignment to platoons. We find that, without competition between groups, individuals are more prone to cooperate altruistically in a prisoner's dilemma game with in-group as opposed to out-group members. They also use a costly punishment option to selectively harm those who defect, encouraging a norm of cooperation towards the group. Adding competition between groups causes even stronger in-group cooperation, but also a qualitative change in punishment: punishment becomes antisocial, harming cooperative and defecting out-group members alike. These findings support recent evolutionary models and have important organizational implications.
Keywords: C72; C91; C93; 330; group membership; competition; punishment; army; experiment; Mitgliedschaft; Gruppenentscheidung; Kooperation; Altruismus; Soziales Verhalten; Schweiz; Test